2021
DOI: 10.1192/j.eurpsy.2021.2219
|View full text |Cite
|
Sign up to set email alerts
|

Is Europe facing an opioid crisis like the United States? An analysis of opioid use and related adverse effects in 19 European countries between 2010 and 2018

Abstract: Authors' Contributions:MP conducted the data collection. WvdB, MP and JvA conducted the data analysis. MP created the figures. WvdB, MP, JvA, GK and AS interpreted the data and created the results. MP wrote the first draft of the report with critical input from WvdB, MP, JvA, GK and AS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(55 citation statements)
references
References 19 publications
6
49
0
Order By: Relevance
“…Opioids are involved in fatal overdose more often than any other drug [1]. The global opioid market is growing, and fatal overdoses related to illicit opioids such as heroin (diamorphine) and to the misuse of opioid painkillers have increased to record levels in the developed world [2]. The UK experiences the most opioid-related deaths of any European nation total and per head of population, with 3,256 deaths recorded in 2017 [3].…”
Section: Introductionmentioning
confidence: 99%
“…Opioids are involved in fatal overdose more often than any other drug [1]. The global opioid market is growing, and fatal overdoses related to illicit opioids such as heroin (diamorphine) and to the misuse of opioid painkillers have increased to record levels in the developed world [2]. The UK experiences the most opioid-related deaths of any European nation total and per head of population, with 3,256 deaths recorded in 2017 [3].…”
Section: Introductionmentioning
confidence: 99%
“…However, the level of prescription opioid use [10] and opioid-related deaths in most European countries is still (much) lower than in the USA. For example, opioid-related mortality in the EU was 1.3 per 100,000 population in 2017 (US: 14.9 per 100,000) [11]. Although opioid-related harm appears limited in the EU as a whole, there are some EU (constituent) countries (e.g., Estonia and Scotland) that reported an opioid-related mortality rate similar to the USA [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, two recent studies have suggested Ireland has relatively high opioid overdose mortality, and that prescribing of strong opioids has increased between 2010 and 2019. 6 , 7 With changing opioids prescribing, it is important to understand if changes are driven by higher prescribing rates or doses/potencies, and also how this fits within the context of other analgesic medications. The potential for inappropriate use and misuse of analgesics is not limited to opioids, with treatments for neuropathic pain, such as pregabalin and gabapentin, also of concern.…”
Section: Introductionmentioning
confidence: 99%
“…In Ireland, although codeine prescribing has been examined, 5 there has been little evidence on trends in opioid prescribing. However, two recent studies have suggested Ireland has relatively high opioid overdose mortality, and that prescribing of strong opioids has increased between 2010 and 2019 6,7 . With changing opioids prescribing, it is important to understand if changes are driven by higher prescribing rates or doses/potencies, and also how this fits within the context of other analgesic medications.…”
Section: Introductionmentioning
confidence: 99%